Safety and efficacy of 23-valent polysaccharide pneumococcal vaccine in patients with systemic lupus erythematosus - G. M. Tarasova; B. S. Belov; M. V. Cherkasova; E. A. Aseeva; T. M. Reshetnyak; T. V. Popkova; N. M. Kosheleva (Современная ревматология)
Objective: to study the safety and efficacy of the 23-valent polysaccharide pneumococcal vaccine (PPV-23) in patients with systemic lupus erythematosus (SLE).Patients and methods. The study included 75 patients with definite diagnosis of SLE at the age of 19–68 years, 10 (13%) of them had high SLE activity, 18 (24%) – moderate, 42 (56%) – low, in 5 (7%) patients the disease was in remission. PPV-23 was injected subcutaneously in a single dose of 0.5 ml. In 60 patients the follow-up period was ≥12 months, in 15 – from 2 to 6 months. Patients were examined before and 1, 3 and 12 months after immunization.Results and discussion. In 38 (50.7%) patients, standard local vaccination reactions of mild and moderate severity were noted, in 1 (1.3%) – a general reaction of mild severity, in 2 (2.7%) – mild diarrhea during 1 day, in 1 (1.3%) – a hyperergic reaction of the Artyus phenomenon type, the symptoms were relieved within 7 days. During 12 months of follow-up, neither exacerbations of SLE, reliably associated with vaccination, nor new autoimmune phenomena, were detected. After 1 year of observation, the number of responders to vaccination was 58%, non-responders – 42%. The duration and activity of the disease, age over 50 years, glucocorticoid therapy > 10 mg per day, did not significantly affect the vaccine response. There was a decrease in the immune response in patients on biologic DMARDs (bDMARDs) therapy compared to patients without such treatment (43 and 68% of cases, respectively), p=0.058. There was no difference between rituximab and belimumab treated subjects. There was a tendency for the prevalence of vaccination responses among patients, who received bDMARDs <1 year before immunization, as well as among patients in whom this therapy was initiated after the administration of PPV-23. There was a positive trend in decrease of pneumonia, acute and exacerbations of chronic bronchitis episodes and sinusitis.Conclusion. Sufficient immunogenicity, good tolerability and clinical efficacy of PPV-23 in patients with SLE, including those who received combined immunosuppressive therapy, have been shown. The use of bDMARDs reduces the number of patients with a vaccine response. The number of responders to vaccination increases when immunization is carried out before the initiation of therapy with bDMARDs or when this therapy is initiated <1 year before immunization. Further long-term prospective studies in large patient cohorts are required.